Digital Marketing Initiative and Business Sustainability in The Hospitality Industry in Rivers State, Nigeria (Zien Journal of Social Sciences and Humanities, 2022)
The study examined the relationship between digital marketing initiative and business sustainability of the hospitality industry in Rivers State, Nigeria. Two objectives, research questions and hypotheses were formulated to guide the study. The population of 171 hospitality organisations with employees of 2514 participated in the study. The sample size of 345 was determined using Taro Yamane formula. A total of 345 questionnaires were distributed to the ten selected hospitality organisations in Rivers State. The descriptive and inferential statistics were conducted using SPSS version. 24. The findings revealed that there is positive and significant relationship between online marketing initiative and sustainability of hospitality business in Rivers State. It equally found that offline marketing initiative has positive and significant relationship with sustainability of hospitality industry. It was concluded that the need to stick to digital marketing of hospitality organisations using online and offline digital marketing strategies becomes the answer to the quest for business sustainability in the hospitality industry. It is recommended that the hospitality industry should employ the services of digital marketers so that incessant launching of new platform can be addressable according to market trends; that the hospitality industry should adopt various social channels for digital marketing of their products and that the hospitality industry should create a forum for customer interaction via online (internet, phone, Whatsapp, etc.)